Fabrication and Optimisation of Cashew Nut Butter from Different Vegetable Oils - Mohammed, Nameer K.; Badrol Hisam, Nurul Afikah; Meor Hussin, Anis Shobirin (Recent Advances in Food Nutrition & Agriculture, 2023)
Background: One of the significant problems with peanut butter is oil separation when the product is opened after some time. The selection of vegetable oil, which acts as a stabiliser, plays a significant role in nut butter's textural and sensory quality. Objective: This study aimed to optimise the formulation of cashew nut butter using response surface methodology (RSM). Four different vegetable oils, namely olive oil, virgin coconut oil, soybean oil and palm oil, were used to select efficient vegetable oil based on its effect on the physicochemical characteristics and sensory evaluation of cashew nut butter. Methods: Thirteen formulations of cashew nut butter from RSM were produced to determine the optimum amount of selected oil (olive oil) and honey. Results: Cashew nut butter stabilised with olive oil showed the best and similar values to commercial peanut butter with the lowest oil separation 3.91% and lower values of texture data of firmness (85.8 g), shear work (87.8 g.sec), stickiness (-27.44 g) and work of adhesion (-36.07 g.sec). The recommended volumes of olive oil and honey for cashew nut butter production were 1.29% and 6.16%, respectively. Consumers favor cashew nut butter, according to sensory analysis' overall acceptance. In terms of nutritional quality, cashew nut butter contains a high amount of fat (47.25%), followed by carbohydrates (24.51%) and protein (16.4%). Conclusion: The type of oil showed significant effects on the stability and spreadability of the produced cashew nut butter.
Keywords: response surface methodology